Assessing Comparators of the Trademarks before Confusion for Establishing Unfair Competition through the Social Network â€“ Georgian Perspective - Jintcharadze, Nukri (European Scientific Journal, ESJ, 2024)
The Article aims to assess regulation of unfair competition through the social network in relation to the trademark by relevant Georgian and international legislation in force. In particular, the Article through comparative analyses describes distinctive matters in the practice of the Georgian National Competition Agency with contrast to best international practice, including case law of EU member states. The Article discuss false and inappropriate advertising using communication means regarding registered trademark and use of internet domain in the context of classifying unfair competition. Besides challenging issues mentioned above, the Article distributes comprehensive study on distinguishing â€œlegal name" and "commercial nameâ€ of trademarks before confusion when using for advertising purposes. Accordingly, the Article examines rule of necessity of the cumulative presence of three established (visual, phonetic and semantic) comparators for determination of confusion between trademarks through the prism of unfair competion legislation.